A critical analysis of exchange control in a South African context - Valodia, Rushika (My University, 2019)
Since the implementation of exchange control, it continues to play a pivotal role in South Africa. In South Africa, exchange control has evolved, specifically there has been a gradual liberalisation in the related rules and regulations. To this extent, it is crucial to consider the relevance of exchange control in South Africa and the potential consequences of repealing the regulations, including the implications on the collection of taxes by the South African Revenue Service (SARS). This research report seeks to explore this. While there have been countries that have maintained its exchange control regulations,there have also been others which have abolished the regulations. The evolution of South Africa’s exchange control will be compared to Mozambique, Iceland and Venezuela. These countries have been selected based on their economic climates, current exchange control limitations and to gauge an understanding of potential challenges and consequences these countries have experienced and those that South Africa will likely face as a result of repealing its exchange control regulations. The South African Reserve Bank (SARB) monitors the imposition of exchange control as the current regulations have control over South African’s foreign currency reserves, accruals and the spending thereof1. SARS and SARB jointly ensure that taxpayers are compliant and that there are no contravention of exchange control regulations2. A key finding arising from the research is the potential effect that the abolishment of exchange control will have in South Africa. The risks and rewards associated with abolishing exchange control regulations has gone unasked and unanswered in academic literature. Finally, as part of the critical analysis of exchange control in South Africa this research report aims to provide a recommendation on the continued liberalisation or potential retraction of exchange control regulations in South Africa, and the mitigations against adverse effects on the parties to exchange control.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Commerce (specialising in Taxation), March 2019
Keywords: UCTD; Authorised Dealer; Authorised Dealer Manual; Common Monetary Area; Financial Surveillance Department; South African Development Community; South African Revenue Service; Money market funds--South Africa; Foreign exchange--Law and legislation--South Africa; Money market--South Africa; SDG-8: Decent work and economic growth